Living with Hope: Resilience Among Parent/s of Children with Autism in Palembang Therapy Center - Hidayati, Diajeng Laily; Aisha, Maulita Noor (INKLUSI, 2022)
In the developing countries, social services for people with disability (PwD) are still limited and responsibility for the development of chil- dren with disability is often associated with their parent/s. The children with special needs, including those with autism, impacts all members of his/her family and leads to the emergence of crisis experiences in the family. The article talks the resiliency of parent/s with autistic chil- dren in Palembang Terapi Center. This paper is written with a phenom- enological approach. Findings show that dominant themes emerged regarding resiliency in this paper setting are self-acceptance, self-ef- ficacy, and adaptation. Several factors that influence the resilience of parents with autistic children are individual abilities, children’s con- ditions, environment, and religious values. Moreover, there are three types of resiliencies according to the level of difficulty experienced by parent/s; high level of difficulty, moderate level of difficulty, and lower level of difficulty. Di negara berkembang, keterbatasan layanan sosial bagi penyandang disabilitas dan tanggung jawab atas tumbuh kembang anak penyandang disabilitas seringkali dikaitkan dengan orang tua. Keberadaan anak berkebutuhan khusus, termasuk anak dengan autisme berdampak pada seluruh anggota keluarga dan berujung pada kemuncul pengalaman krisis keluarga. Artikel ini mengeksplorasi resiliensi orang tua yang memiliki anak dengan autisme di Pusat Terapi Palembang. Artikel ini ditulis dengan pendekatan fenomenologis. Temuan menunjukkan tema terkait resiliensi dalam penerimaan diri, efikasi diri, dan adaptasi. Temuan lain adalah faktor yang mempengaruhi resiliensi orang tua yang memiliki anak autisme dengan kemampuan individu, kondisi anak, lingkungan, dan nilai agama. Selain itu, ada tiga jenis resiliensi menurut tingkat kesulitan yang dialami orang tua; tingkat kesulitan tinggi, sedang, dan rendah.